Incidence of inflammatory breast cancer in patients with clinical inflammatory breast symptoms. - Yohann Dabi; Lauren Darrigues; Kelly Pons; Mylène Mabille; Issam Abd Alsamad; Rana Mitri; Dounia Skalli; Bassam Haddad; Cyril Touboul (PLoS ONE, 2017)
To describe a large cohort of women with non-puerperal inflammatory breast and to identify characteristics of inflammatory breast cancer.All patients consulting for inflammatory breast syndrome in the breast unit of our tertiary University hospital between September 2013 and December 2015 were prospectively included. We excluded women who were pregnant or in the postpartum period. Patients underwent systematic clinical examination and imaging (breast ultrasonography and mammography). A biopsy was performed if the clinician suspected a malignant lesion of the breast. Clinicopathologic and radiologic data were registered. Statistics were performed using R (3.0.2 version) software.Among the 76 patients screened and included, 38 (50%) had a malignant lesion at final diagnosis, 21 (27.6%) were diagnosed with infectious disease and 17 (22.4%) with inflammatory disease of the breast. When compared to patients with benign disease, patients with a malignant lesion were significantly older (p = 0.022, CI95% 1.78-14.7), had a significantly bigger palpable mass (p<0.001, CI 95% 22.8-58.9), were more likely to have skin thickening (p = 0.05) and had more suspicious lymph nodes at clinical examination (p<0.001, CI 95% 2.72-65.3). Precise limits on ultrasonography were significantly associated with benign lesions. The presence of a mass (p = 0.04), micro calcifications (p = 0.04) or of focal asymmetry (p<0.001, CI95% 1.3-618) on mammography was significantly associated with malignant disease.Inflammatory breast cancer was common in our cohort of women consulting for inflammatory breast syndrome. Identifying these patients with high-risk malignancy is crucial in the management of an inflammatory breast.